The influence of physiotherapy on the treatment of inflammatory bowel diseases – a short overview - Wrzesiński, Bartłomiej; Piechocka, Edyta; Wojtczak, Paweł; Ziółkowska, Anna; Szustka, Angelika; Balcerska, Kamila; Bielejewska, Marta; Łopatka, Patrycja (Journal of Education, Health and Sport, 2018)
Background of Inflammatory diseases of the intestines affect more and more people, this is caused not only by genetic determinants but also by environmental conditions and lifestyle. Lack of physical activity may affect the symptoms of the disease and increase their intensity, therefore during the remission of the disease it is recommended to use training and physiotherapeutic techniques to reduce the symptoms, such as pain, fatigue or reduced quality of life. The below systematic review shows the impact of individual physical trainings and physiotherapeutic techniques on symptoms resulting from inflammatory bowel diseases.